Peningkatan Profesionalisme Guru Pendidikan Agama Islam melalui Metode Kunjung Karya: Studi Kasus Kualitatif - Firdayeni Firdayeni; Fadriati Fadriati; Ermis Suryana (Lembaga Yasin AlSys, 2026)
Although the professionalism of Islamic Religious Education (PAI) teachers has been the focus of numerous previous studies, research that specifically examines the kunjung karya method as an instrument for developing PAI teacher professionalism remains relatively limited. This study aimed to analyze the contribution of implementing the kunjung karya method to enhancing the professionalism of PAI teachers, particularly in the aspects of lesson planning, instructional implementation, and learning evaluation. The study employed a qualitative approach with a case study design, involving one PAI teacher and students at SMPN 2 Rambatan selected through purposive sampling. Data were collected through classroom observations, in-depth interviews, and documentation of learning devices, and were then analyzed using thematic analysis techniques through data reduction, data display, and conclusion drawing. The findings show that the implementation of the kunjung karya method encourages PAI teachers to design instruction more systematically, to conduct active, collaborative, and student-centered learning, and to carry out comprehensive and reflective learning evaluation. These results contribute to strengthening teacher professionalism theory that emphasizes reflective practice and active-collaborative learning, while also broadening understanding of PAI teacher professionalism development based on classroom practice. The study concludes that the kunjung karya method is an important pedagogical strategy and a vehicle for professional development for PAI teachers, with theoretical implications for teacher professionalism studies and practical implications for teachers, schools, and education supervisors in improving the quality of PAI instruction, as well as opening opportunities for further research in broader contexts and methodological designs.